Essentials of radiologic science - Fosbinder, Robert (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2010)
"LWW is proud to introduce Essentials of Radiologic Science, a core, comprehensive textbook for radiologic technology students. Focusing on covering the crucial components and minimizing extraneous content, this text will help prepare students for success on the The American Registry of Radiologic Technologists Examination in Radiography and beyond into practice. Topics covered include radiation protection, equipment operation and quality control, image production and evaluation, and patient care. This is a key and crucial resource for radiologic technology programs, focusing on providing relevancy and offering tools and resource to students of multiple learning types. These include a full suite of ancillary products, a variety of pedagogical features imbedded in the text, and a strong focus on the practical application of the concepts presented"--Provided by publisher.